Concurrent recovery of mechanical and electrical properties in nanomodified capsule-based self-healing epoxies. (16th June 2021) - Kosarli, Maria; Foteinidis, Georgios; Tsirka, Kyriaki; Bekas, Dimitrios G.; Paipetis, Alkiviadis S.
Abstract: We propose a novel self-healing capsule based polymer system for the concurrent recovery of electro-mechanical properties and demonstrate for the first time the successful monitoring of the damage and healing process with a real time monitoring of the change of the electrical resistance. Urea-formaldehyde (UF) microcapsules containing an epoxy resin modified with multi-walled carbon nanotubes (MWCNTs) were prepared via in-situ emulsification polymerization. MWCNTs were beneficial to mechanical performance, which was even enhanced, in contrast to typical systems where the inclusion of the healing agent deteriorates performance. The capsule shell morphology and mean diameter were characterized via Scanning Electron Microscopy (SEM) and optical microscopy, while thermogravimetric analysis confirmed a high thermal stability of about 222 °C. Fracture toughness tests and impedance spectroscopy were employed to assess healing. The MWCNT microcapsule enhanced epoxy exhibited an impressive 22% improvement compared to the virgin system followed by a self-healing efficiency of 80% in mechanical and 95% in electrical properties. Graphical abstract: Image 1 Highlights: UF microcapsules with nanomodified healing agent for self-healing materials. Monitoring of the healing process via impedance spectroscopy. Concurrent restoration of mechanical & electrical properties of epoxies. Enhanced healing efficiency.